Where's the P in PG? an analysis connecting Filipino parenting patterns with viewing of "Parental Guidance" rated programs on television with children - Molina, Menard Edu M. (2008)
Television (TV) can be found in most households in the country, broadcasting numerous programs that aim to inform and entertain. Its contents are watched every day by thousands of audiences at a single time, and most practically consider it a calendar and clock by using the programs as guides. TV sets at home are usually the centerpiece of rooms - the focal point in which members of the household would gather. In rural communities, people gather at the window of a "better off," meaning television-owning neighbor. Watching television has become a familial and communal activity for Filipinos. Research in the mass media has more or less kept aside the issue of the family as audience. Media scholars treat the family only as a part of the natural viewing group or target audience. It is for this reason that studying the relationship among parenting practices, structure of Filipino families and the consumption of the PG (parental guidance) - rated television programs becomes important. As television watching is a social activity at the Filipino home, it is important to consider the disparity that the PG-intended programs bring into the equation. This study analyzed the consumption of participant parents residing in households in urban communities in Laguna, specifically in the municipalities of San Pedro, Biñan, and Sta. Rosa, and focused on the actual interaction of the parents (whether biological or surrogate) and/or the guardians with the children during viewing of PG-rated TV programs. The viewing environment, the activities the family undergoes while watching the program, and the parenting practices in the particular households were also factored in the study, to identify the actions that parents take when they watch these programs, and to trace the factors that could affect the parents-children interaction in TV viewing. Based on the data gathered, including those in a previous study, parents do notice and understand the PG warnings on television and the possible effects that TV can give to children. Despite this awareness, parents do not mediate over their children's television viewing. Whether the parenting pattern in a family is strict or more lenient, parents are inclined to use the television in its limited ways: as a pleasure and entertainment tool, as an instrument to keep children preoccupied while they are unavailable because of work or chores, and as a form of reward and punishment for their children. Moreover, the study stresses that parents should be more responsible for their children's well-being by mediating over any TV program, with or without the PG rating. This will lead to a habitual reinforcement of the real meaning of the PG rating.
Includes bibliographical references (pages 40-42).